THE EFFECT OF INTERNATIONAL SOCCER GAMES ON EXCHANGE RATES USING EVIDENCE FROM TURKEY - DEMIR , Ender; LAU, Chi Keung Marco; FUNG, Ka Wai Terence (Journal of Advanced Studies in Finance; Vol 5 No 2 (2014): JASF Volume V, Issue 2(10), Winter, 2014, 2014)
This paper examines the impact of international soccer games of three major soccer clubs of Turkey (Besiktas, Fenerbahce, and Galatasaray), as well as the Turkish national team on Turkish Lira (TL) against the U.S. dollar and TL against Euro during the period between 2003 and 2010. We find that draws and losses do not affect the exchange rates. However, when the effect of wins for each team is analyzed, it is found that a win effect exists only for the Turkish national team. Early studies found that TL tends to depreciate after a Turkish soccer club win over foreign rivals. However, a depressing effect after a win is rare in the literature. This study provides evidence that local currency actually appreciates after a win.